The Union Army’s Surgical Handbook and the Positive Story of Civil War Surgery - John M. Harris, Jr., MD (Annals of Surgery Open)
Western armies have relied on surgical field manuals to help physicians deal with unfamiliar combat medical conditions from the Napoleonic wars to the present day, but there has been little discussion of whether these handbooks have been used or improved outcomes. Recent research shows that the Union Army’s American Civil War (1861–1865) surgical case fatality rates improved as the war progressed, much like the US Army’s experience in later wars, and were generally superior to comparable European results. These positive Civil War outcomes have been attributed to field experience, adoption of best practices, and enhanced communication, without consideration of New York surgeon Stephen Smith’s widely-used Hand-Book of Surgical Operations. The Army of the Potomac added Smith’s pocket-sized Hand-Book to its supply table in 1862. Northern medical journals applauded it, and Smith’s contemporaries documented its wide use. Smith’s handbook explained and demonstrated surgical techniques that were adopted as the war progressed, such as the use of general anesthesia and limb-sparing resection (debridement) of gunshot wounds. It offered pithy, well-documented advice from recognized experts along with numerous illustrations, which allowed untrained physicians to visualize anatomical relationships and see contemporary best practices in a way that no other wartime publication provided, making it an exemplar of a mass-media surgical improvement change agent.